KONTRIBUSI OTOT LENGAN TERHADAP HASIL SERVIS ATAS DALAM PERMAINAN BOLA VOLI EKSTRAKULIKULER SMPN 2 JUJUHAN - Noprian Dwi Saputra; Jhony Hendra; Desi Tri Susanti (Master of Physical Culture and Recreation in Nusantara, 2025)
This study was motivated by the importance of arm muscle explosive power in supporting basic volleyball techniques, particularly the overhand serve. The overhand serve is one of the essential basic skills that significantly determines the flow of the game, thus requiring good physical condition, especially strength and arm explosive power. This research aimed to determine the relationship between arm muscle explosive power and overhand serve ability among students participating in volleyball extracurricular activities at SMP Negeri 2 Jujuhan. This research employed a descriptive method with a correlational approach. The population consisted of 20 students who participated in volleyball extracurricular activities, all of whom were taken as the sample. Data were collected using a push-up test to measure arm muscle explosive power and an overhand serve test to measure serving ability. The data were analyzed using the Kolmogorov-Smirnov normality test, descriptive statistics, and Pearson product-moment correlation with the aid of SPSS software. The results showed that most students’ push-up ability was in the poor and very poor categories, whereas most students’ overhand serve ability was in the good category. The product-moment correlation analysis indicated a significant relationship between arm muscle explosive power and overhand serve ability, with a correlation coefficient of 0.509 and a significance value of 0.022. It can be concluded that arm muscle explosive power contributes to students’ overhand serve performance in volleyball extracurricular activities.